Obesity: a challenge for emergency medical teams—a narrative review - Czapla, Michał; Juárez-Vela, Raúl; Mickiewicz, Aleksander; Raczyński, Andrzej; Griesmann, Krzysztof; Kędzierski, Kamil; Wojciechowski, Jakub; Burzński, Michał; Fedorowicz, Olga; Koral, Mariusz; Kowalczyk, Damian; Smereka, Jacek (Frontiers in Public Health, 2025)
The global rise in obesity presents significant challenges for emergency medical services (EMS), particularly in prehospital care settings. This narrative review examines the multifaceted impact of obesity on emergency interventions, focusing on airway management, resuscitation, vascular access, pharmacological considerations, transport logistics, and point-of-care ultrasound. Evidence indicates that excess adipose tissue alters the biomechanics of chest compressions, increases thoracic bioimpedance during defibrillation, and complicates airway management—especially in cases when advanced airway devices are required. Additionally, pharmacokinetic and pharmacodynamic differences in this population necessitate careful dose adjustment based on drug solubility and body composition. Obtaining vascular access in individuals with obesity is frequently hampered by anatomical constraints, often requiring ultrasound-guided cannulation or intraosseous access. Prehospital transport introduces additional logistical and ergonomic challenges, exacerbated by limited availability of appropriately sized equipment, weight-restricted airframes in Helicopter Emergency Medical Service (HEMS) operations, and difficulty in transferring patients from the scene. Meanwhile, ultrasonographic imaging is technically more demanding and often diagnostically limited in this group due to tissue depth and image degradation. These factors collectively compromise both the speed and quality of emergency care. This review highlights the importance of developing tailored protocols, specialized equipment, and targeted training for Emergency Medical System (EMS) providers who manage patients with obesity. Given the increasing prevalence of patients with obesity in the emergency setting, early identification and anticipatory planning are critical for improving patient outcomes. Addressing these operational and clinical challenges must become a priority for modern EMS.